МОНГОЛЫН ХӨРӨНГИЙН БИРЖИЙН БҮТЭЭГДЭХҮҮНИЙ ҮЗҮҮЛЭЛТИЙН ЗАРИМ СУДАЛГАА, ДҮГНЭЛТ - Б.Хүрэлбаатар; Б.Болор (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
This research is to define last 10 years and/or 2007-2016 main factors of the financial ratios and share market value of the 53 companies ranked I and II at MSE (Mongolian Stock Exchange) represent 16 different sectors. At the end of 2016, Mongolia’s share turnover is 3.3% lower than comparing to other developing country’s market, stocks registered at the Stock exchange are too centralized, securities trading takes only 14.1% of total trade at MSE, 78% of listed companies are being not accountable for their responsibilities. Moving forward and to achieve better result, we need to promote the stock market operation, increase its compatibility at international markets, provide better opportunities for companies to collect their financial resources, to offer wide variety of products that meets investors specific needs and at last both companies and investors need to work more proactive.